Implementation and Empirical Analysis of ACCA Model Optimized by Learning Management System to Enhance the Students’ Creative Thinking Skills - Muharni, Andi; Mahanal, Susriyati; Zubaidah, Siti; Susanto, Hendra (Society of Visual Informatics, 2025)
The ability to think creatively is one of the essential competencies that must be developed in the education process in the modern era.Creative thinking skills can be stimulated through the application of the right learning model. One of the learning models that can help educators stimulate creative thinking skills is the ACCA learning model. The purpose of this research is to analyze and describe the effect of ACCA learning model on improving creative thinking skills. This study used an experimental research design with pre-test-post-three-treatment conducted at one of the State Universities in Makassar, Indonesia. The implementation of ACCA learning model assisted by the Learning Management System (LMS) to optimize the use of technology and improve creative thinking skills. The research instrument used in this study was an integrated essay test of creative thinking skills that had gone through a validity and reliability process. Data collection was based on the results of students' answers at the time of the pre-test and post-test. The statistical analysis used in this study was Ancova test with a significance level of 0.05. The results of the data analysis showed that the ACCA learning model assisted by LMS can improve creative thinking skills. The flexibility offered by this model provides opportunities for students to express themselves and be active in learning and solving problems faced both independently and in groups. Based on these findings, this research can be used as one of the innovative models in empowering creative thinking skills and other skills of students.